La agricultura familiar y la inclusión productiva: un factor contribuyente a la paz - Berry, Albert (Revista Colombiana de Ciencias Pecuarias, 2017)
Small family agriculture offers the only sure basis for significant improvements in the earnings of lower-income families in Colombia, a conclusion due in part to the potential dynamism of this sector and in part to the lack of alternatives.